Propylene-based copolymer composition for pipes

CN122996121APending Publication Date: 2026-10-27BASELL POLIOLEFINE ITALIA SRL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202580023793.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-30
Filing Date
2025-03-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

通常在基于聚丙烯的组合物中,当冲击性能提高时,挠曲模量降低

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

A polyolefin composition comprising: A) from 85 wt% to 99.0 wt% of a propylene homopolymer; B) from 1.0 wt% to 15.0 wt% of a propylene, ethylene copolymer composition having: iii) an intrinsic viscosity measured in tetrahydronaphthalene of a fraction soluble in xylene at 25°C ranging from 5.7 dl / g to 9.2 dl / g; the propylene, ethylene copolymer composition component B) comprising: b1) from 27 wt% to 40 wt% of a propylene homopolymer having a melt flow rate MFR1 (230°C / 2.16 kg, ISO 1133) ranging from 62.0 g / 10 min to 100.0 g / 10 min; b2) from 27 wt% to 40 wt% of a propylene homopolymer having melt flow rate MFR2 (230°C / 2.16 kg, ISO 1133) lower than MFR1; b3) from 20 wt% to 46 wt% of a propylene ethylene copolymer having an ethylene derived units content ranging from 18.0 wt% to 48.0 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a composition comprising a propylene homopolymer and a heteropolymer propylene-ethylene copolymer, which is particularly suitable for the production of sewage pipes with relatively high impact resistance at low temperatures to ensure installation under low-temperature conditions. Background Technology

[0002] Propylene-ethylene copolymers are known in the art to be used in the production of pipes.

[0003] For example, according to international patent application WO 97 / 33117, pipes made of polypropylene plastic material with high creep resistance, high long-term pressure resistance, improved stiffness, and resistance to rapid crack propagation can be obtained. According to the aforementioned document, catastrophic failure of the polypropylene plastic pipe can be prevented when it is made of several layers of different polypropylene plastic materials, wherein at least one layer consists of a wide molecular weight distribution (MWD) polypropylene providing high creep resistance, and at least one layer consists of an elastomer-modified polypropylene with improved impact strength. The wide MWD polypropylene is a mixture of an extremely high molecular weight propylene random copolymer having 1% to 10% by weight of ethylene or higher α-olefin repeating units and a low molecular weight propylene polymer having low (at most 1% by weight) or zero comonomers.

[0004] Limiting the wall thickness of pipes is important. This allows for pipes with less material and lighter weight, and improves feeding efficiency due to the larger inner diameter (primarily for smaller diameter pipe applications). However, as the wall thickness decreases, the pipe becomes brittle, necessitating the use of materials with high impact resistance, especially at low temperatures. Furthermore, the material used for the pipe must have a high flexural modulus to achieve a rigid pipe. Typically, in polypropylene-based compositions, the flexural modulus decreases as impact performance increases. The applicant has discovered that a small amount of a heterogeneous copolymer with certain characteristics can be added to a propylene-ethylene copolymer to achieve a good impact / stiffness balance without substantially compromising stiffness. Summary of the Invention

[0005] The purpose of this disclosure is to provide a polyolefin composition comprising:

[0006] A) 85% to 99.0% by weight of a propylene homopolymer, wherein the propylene homopolymer has:

[0007] (i) Polydispersion index ranging from 5 to 10

[0008] (ii) 4.0% to 1.0% by weight of xylene solubles at 25°C;

[0009] (iii) Melt flow rate (230°C / 5kg, ISO 1133), which ranges from 0.2 g / 10 min to 3.5 g / 10 min;

[0010] B) A propylene-ethylene copolymer composition comprising 1.0% to 15.0% by weight, wherein the propylene-ethylene copolymer composition has the following characteristics:

[0011] i) Fractions ranging from 20% to 38% by weight that are soluble in xylene at 25°C;

[0012] ii) Melt flow rate (230°C / 2.16 kg, ISO 1133), which ranges from 0.4 g / 10 min to 4.0 g / 10 min;

[0013] iii) The intrinsic viscosity of the fractions of xylene soluble at 25 °C, ranging from 5.7 dl / g to 9.2 dl / g, measured in tetrahydronaphthalene;

[0014] Component B of the propylene-ethylene copolymer composition comprises:

[0015] b1) 27% to 40% by weight of propylene homopolymer, wherein the melt flow rate MFR1 (230°C / 2.16 kg, ISO 1133) of the propylene homopolymer ranges from 62.0 g / 10 min to 100.0 g / 10 min;

[0016] b2) 27% to 40% by weight of propylene homopolymer, wherein the melt flow rate MFR2 (230°C / 2.16 kg, ISO 1133) of the propylene homopolymer is lower than that of MFR1;

[0017] b3) 20% to 46% by weight of a propylene-ethylene copolymer, wherein the ethylene-derived unit content of the propylene-ethylene copolymer ranges from 18.0% to 48.0% by weight.

[0018] The melt flow rate (230°C / 5kg, ISO 1133) of the polyolefin composition ranges from 0.4 g / 10 min to 4.0 g / 10 min; the total amount of A+B is 100% by weight and the total amount of b1+b2+b3 is 100% by weight. Detailed Implementation

[0019] Therefore, the object of this disclosure is a polyolefin composition comprising:

[0020] A) 85.0% to 99.0% by weight; preferably 90% to 98.5% by weight; more preferably 93% to 98% by weight of a propylene homopolymer, the propylene homopolymer having:

[0021] (i) Polydispersion index ranging from 5 to 10

[0022] (ii) 4.0% to 1.0% by weight; preferably 3.0% to 2.0% by weight of the xylene solubles at 25°C;

[0023] (iii) Melt flow rate (230°C / 5kg, ISO 1133), which ranges from 0.2 g / 10 min to 3.5 g / 10 min; preferably from 0.6 g / 10 min to 2.0 g / 10 min;

[0024] B) 1.0% to 15.0% by weight; preferably 90% to 98.5% by weight; more preferably 2.0% to 7.0% by weight of a propylene-ethylene copolymer composition, the propylene-ethylene copolymer composition having:

[0025] i) A fraction ranging from 20.0% to 38.0% by weight; preferably from 22.0% to 36.0% by weight; more preferably from 25.0% to 33.0% by weight of a fraction soluble in xylene at 25°C;

[0026] ii) Melt flow rate (230°C / 2.16 kg, ISO 1133), which ranges from 0.4 g / 10 min to 4.0 g / 10 min; preferably from 0.6 g / 10 min to 3.0 g / 10 min; more preferably from 0.8 g / 10 min to 2.2 g / 10 min;

[0027] iii) The intrinsic viscosity of a fraction soluble in xylene at 25°C, ranging from 5.7 dl / g to 9.2 dl / g; preferably from 6.0 dl / g to 8.75 dl / g; more preferably from 6.2 dl / g to 8.2 dl / g, as measured in tetrahydronaphthalene;

[0028] The propylene-ethylene copolymer composition comprises:

[0029] b1) 27% to 40% by weight; preferably 29% to 38% by weight; more preferably 30% to 36% by weight of a propylene homopolymer, wherein the melt flow rate MFR1 (230°C / 2.16 kg, ISO 1133) of the propylene homopolymer ranges from 62.0 g / 10 min to 100.0 g / 10 min, preferably 72 g / 10 min to 87 g / 10 min, more preferably 76 g / 10 min to 84 g / 10 min;

[0030] b2) 27% to 40% by weight; preferably 29% to 38% by weight; more preferably 30% to 36% by weight of a propylene homopolymer, wherein the melt flow rate MFR2 (230°C / 2.16 kg, ISO 1133) of the propylene homopolymer is lower than MFR1; preferably lower than MFR1 - 40 g / 10 min; more preferably lower than MFR1 - 65 g / 10 min;

[0031] b3) 20% to 46% by weight, preferably 24% to 42% by weight; more preferably 28% to 40% by weight of a propylene-ethylene copolymer, wherein the ethylene-derived unit content of the propylene-ethylene copolymer ranges from 18.0% to 48.0% by weight; preferably 22% to 44% by weight; more preferably 27% to 39% by weight;

[0032] The melt flow rate (230°C / 5kg, ISO 1133) of the polyolefin composition ranges from 0.4 g / 10 min to 4.0 g / 10 min; preferably from 0.7 g / 10 min to 3.2 g / 10 min; more preferably from 1.0 g / 10 min to 2.7 g / 10 min; the total amount of A+B is 100% by weight and the total amount of b1+b2+b3 is 100% by weight.

[0033] The term copolymer refers to a polymer containing only two monomers, preferably propylene and ethylene.

[0034] The polyolefin compositions disclosed herein preferably exhibit a Charpy impact test measured at 23°C according to ISO 179-1:2010, with a Charpy impact range of 55.0 kJ / m. 2 Up to 80.0 KJ / m 2 The preferred range is 60.0 KJ / m³. 2 Up to 75.0 KJ / m 2 Even more preferably, the range is 63.0 KJ / m 2 Up to 72.0 KJ / m 2 The tensile modulus of the polyolefin compositions disclosed herein, as determined according to ISO 527-2, ranges from 1700 MPa to 2500 MPa; preferably from 1800 MPa to 2300 MPa; and even more preferably from 1900 MPa to 2200 MPa. The flexural modulus of the polyolefin compositions disclosed herein, as determined according to ISO 178:2019, ranges from 1600 MPa to 2400 MPa; preferably from 1700 MPa to 2200 MPa; and even more preferably from 1800 MPa to 2100 MPa.

[0035] Using the polyolefin compositions disclosed herein, pipes with high modulus and high impact resistance can be obtained, particularly sewage pipes. In particular, impact resistance can be improved without reducing modulus.

[0036] Therefore, another object of this disclosure is a conduit comprising the composition of this disclosure.

[0037] As used herein, the term "pipe" also includes pipe fittings, valves, and all components typically required for systems such as hot water piping. The definition also includes single-layer and multi-layer pipes, where one or more layers are, for example, metallic layers and may include adhesive layers.

[0038] Such articles can be manufactured by various industrial methods well known in the art, such as molding, extrusion, etc.

[0039] In other embodiments of this disclosure, the compositions further comprise, relative to 100 parts by weight, an amount ranging from 0.5 to 60 parts by weight of an inorganic filler. Typical examples of such fillers are calcium carbonate, barium sulfate, titanium dioxide, and talc. Talc and calcium carbonate are preferred. Many fillers can also have a nucleating effect, such as talc, which is also a nucleating agent. The amount of nucleating agent is typically from 0.2% to 5% by weight relative to the amount of polymer.

[0040] The compositions disclosed herein are also suitable for providing pipes having walls with any configuration other than those having smooth inner and outer surfaces. Examples are pipes with sandwich-like pipe walls, pipes with hollow wall structures having longitudinally extending cavities, pipes with hollow wall structures having helical cavities, and pipes having smooth inner surfaces and compact or hollow, helical or annular ribbed outer surfaces, regardless of the configuration of the respective pipe ends.

[0041] Articles, pressure pipes and related fittings according to this disclosure are manufactured in a manner known per se, such as by (co)extrusion or molding.

[0042] The extrusion of the product can be carried out using different types of polyolefin extruders (such as single-screw or twin-screw extruders).

[0043] Another embodiment of this disclosure is a method of molding the composition into the article.

[0044] When the conduit is multilayered, at least one layer is made of the above-described polyolefin composition. The additional layers are made of amorphous or crystalline polymers of R-CH=CH2 olefins (such as homopolymers and copolymers or terpolymers), wherein R is a hydrogen atom or a C1-C6 alkyl group. Particularly preferred polymers are:

[0045] Isotropic or predominantly isotactic propylene homopolymers;

[0046] Random copolymers and terpolymers of propylene with ethylene and / or C4-C8 α-olefins (such as 1-butene, 1-hexene, 1-octene, 4-methyl-1-pentene), wherein the total monomer content ranges from 0.05% by weight to 20% by weight, or the polymer is a mixture with isotactic or predominantly isotactic propylene homopolymers.

[0047] A heterogeneous polymer blend comprising: (a) a propylene homopolymer, and / or a copolymer of item (2) and a terpolymer; and an elastomer portion (b) comprising a copolymer of ethylene with propylene and / or a C4-C8 α-olefin and a terpolymer (optionally containing trace amounts of diene, the same substance disclosed for polymer (2)(a)); and

[0048] Amorphous polymers, such as fluorinated polymers and polydifluoroethylene (PVDF).

[0049] In multi-layered pipes, the layers of pipe can have the same or different thicknesses.

[0050] The compositions disclosed herein can be prepared by blending various components A), b1), b2) and b2), or by preparing component A) and blending it with component B) prepared in a single polymerization process via a sequential polymerization step.

[0051] The polymerization of A) and B) can be carried out in the presence of a Ziegler-Natta catalyst. An essential component of the catalyst is a solid catalyst component comprising a titanium compound having at least one titanium-halogen bond and an electron donor compound, both supported in active form on magnesium halides. Another essential component (co-catalyst) is an organoaluminum compound, such as an alkylaluminum compound.

[0052] External donors can be added optionally.

[0053] The catalysts commonly used in the methods disclosed herein are capable of producing polypropylene with a xylene insolubility value greater than 90%, preferably greater than 95%, at ambient temperature.

[0054] Catalysts possessing the above-described features are well known in patent literature; those described in U.S. Patent 4,399,054 and European Patent 45,977 are particularly advantageous. Other examples can be found in U.S. Patent 4,472,524.

[0055] The solid catalyst components used in the catalyst include compounds selected from the group consisting of: ethers, ketones, lactones, compounds containing N, P and / or S atoms, and esters of monocarboxylic acids and dicarboxylic acids.

[0056] Particularly suitable electron donor compounds are phthalic acid esters and 1,3-diethers of the following formula:

[0057]

[0058] Wherein RI and RII are the same or different and are C1-C18 alkyl, C3-C18 cycloalkyl, or C7-C18 aryl; RIII and RIV are the same or different and are C1-C4 alkyl; or are 1,3-diethers, wherein the carbon atom at position 2 belongs to a cyclic or polycyclic structure consisting of 5, 6, or 7 carbon atoms or 5-n or 6-n' carbon atoms and n nitrogen atoms and n' heteroatoms selected from the group consisting of N, O, S, and Si, where n is 1 or 2 and n' is 1, 2, or 3, and the structure contains two or three degrees of unsaturation ( A cyclic polyene structure, and optionally condensed with other cyclic structures, or substituted with one or more substituents selected from the group consisting of: straight-chain or branched alkyl, cycloalkyl, aryl, aralkyl, alkylaryl, and halogen, or condensed with other cyclic structures and substituted with one or more of the above substituents, one or more of the above substituents may also be bonded to the condensed cyclic structure; one or more of the above alkyl, cycloalkyl, aryl, aralkyl, or alkylaryl and optionally containing one or more heteroatoms as substituents of carbon or hydrogen atoms or both.

[0059] This type of ether is described in published European patent applications 361493 and 728769.

[0060] Representative examples of the diethers are 2-methyl-2-isopropyl-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-dimethoxypropane, 2-isopropyl-2-cyclopentyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, and 9,9-bis(methoxymethyl)fluorene.

[0061] Other suitable electron donor compounds are phthalic acid esters, such as diisobutyl phthalate, dioctyl phthalate, diphenyl phthalate, and benzyl butyl phthalate.

[0062] The preparation of the above catalyst components is carried out according to various methods.

[0063] For example, MgCl2 • nROH adducts (especially in spherical particulate form) (where n is typically from 1 to 3 and ROH is ethanol, butanol, or isobutanol) react with an excess of TiCl4 containing an electron donor compound. The reaction temperature is typically 80°C to 120°C. The solid is then separated and reacted again with TiCl4 in the presence or absence of the electron donor compound, followed by separation and washing with an aliquot of hydrocarbons until all chloride ions are removed.

[0064] In the solid catalyst composition, titanium compounds, represented as Ti, are typically present in an amount of 0.5 wt% to 10 wt%. The amount of electron donor compounds retained on the solid catalyst composition relative to magnesium dihalide is typically 5 mol% to 20 mol%.

[0065] Titanium compounds that can be used to prepare solid catalyst components are titanium halides and halogen alcohols. Titanium tetrachloride is a preferred compound.

[0066] The above reactions form magnesium halides in their active form. Other reactions are known in the literature, which begin with magnesium compounds other than halides (such as magnesium carboxylate) to form magnesium halides in their active form.

[0067] Alkyl aluminum compounds used as cocatalysts include trialkyl aluminum, such as triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, and linear or cyclic Al-alkyl compounds containing two or more Al atoms bonded to each other by O or N atoms or SO4 or SO3 groups.

[0068] Al-alkyl compounds are typically used in amounts that result in an Al / Ti ratio of 1 to 1000.

[0069] Electron donor compounds that can be used as external donors include aromatic esters, such as alkyl benzoates, and in particular silicon compounds containing at least one Si-OR bond, where R is a hydrocarbon group.

[0070] Examples of silicon compounds are (tert-butyl)2Si(OCH3)2, (cyclohexyl)(methyl)Si(OCH3)2, (cyclopentyl)2Si(OCH3)2, (phenyl)2Si(OCH3)2, and (1,1,2-trimethylpropyl)Si(OCH3)3.

[0071] 1,3-diethers having the above chemical formula can also be advantageously used. If the internal donor is one of these diethers, the external donor can be omitted.

[0072] In particular, even though many other combinations of the aforementioned catalyst components may allow for the preparation of compositions according to this disclosure, components A) and B) are preferably prepared by using a catalyst containing phthalate as an internal donor and (cyclopentyl)2Si(OCH3)2 as an external donor, or the 1,3-diether as an internal donor.

[0073] Additionally, the Ziegler-Natta catalyst that can be used to prepare the propylene polymer of this disclosure is a solid catalyst component comprising magnesium halide, a titanium compound having at least one titanium-halogen bond as described above, and at least two electron donor compounds, one of which is selected from succinates and the other from 1,3-diethers.

[0074] Component A is preferably produced using the polymerization method shown in EP application 1,012,195.

[0075] Specifically, the method includes: feeding monomers into the polymerization zone under reaction conditions in the presence of a catalyst, and collecting polymer products from the polymerization zone. In this method, grown polymer particles flow upwards through one (first) polymerization zone (riser) of the polymerization zone under rapid fluidization conditions, exit the riser and enter another (second) polymerization zone (downstream) through which they flow downwards in a densified form under gravity, exit the downstream and are reintroduced into the riser, thereby establishing a polymer circulation between the riser and the downstream.

[0076] In the downcomer, a high solids density is achieved, approaching the bulk density of the polymer. Therefore, a positive pressure gain can be obtained along the flow direction, allowing the polymer to be reintroduced into the riser without the aid of special mechanical devices. In this way, a "loop" circulation is established, defined by the pressure balance between the two polymerization zones and the head loss introduced into the system.

[0077] Typically, rapid fluidization conditions in the riser are established by feeding a gas mixture containing the relevant monomers into the riser. Preferably, the gas mixture is fed below the point where the polymer is reintroduced into the riser by using a gas distributor device where appropriate. The velocity of the delivery gas entering the riser is higher than the delivery velocity under operating conditions, preferably 2 m / s to 15 m / s.

[0078] Typically, the polymer and gas mixture exiting the riser is conveyed to a solid / gas separation zone. Solid / gas separation can be achieved using conventional separation methods. The polymer enters the downcomer from the separation zone. The gaseous mixture exiting the separation zone is compressed, cooled, and transferred to the riser, with supplementary monomers and / or molecular weight modifiers added, if appropriate. Transfer can be achieved via a gas mixture recirculation line.

[0079] Control of the polymer circulating between the two polymerization zones can be achieved by metering the amount of polymer leaving the downcomer using a device suitable for controlling solid flow, such as a mechanical valve.

[0080] The operating parameters (such as temperature) are those commonly used in olefin polymerization methods, for example, between 50°C and 120°C.

[0081] The first stage process can be carried out at an operating pressure between 0.5 MPa and 10 MPa, preferably between 1.5 MPa and 6 MPa.

[0082] Advantageously, one or more inert gases are maintained in the polymerization zone in an amount such that the sum of the partial pressures of the inert gases is preferably between 5% and 80% of the total gas pressure. The inert gases may be, for example, nitrogen or propane.

[0083] Various catalysts can be fed upwards into the riser at any point. However, they can also be fed at any point in the downcomer. The catalyst can be in any physical state, so solid or liquid catalysts can be used.

[0084] The following examples are given to illustrate this disclosure and not to limit its scope.

[0085] Example

[0086] Characterization methods

[0087] Xylene-soluble (XS) fraction at 25°C

[0088] The xylene soluble content at 25°C has been determined according to ISO 16 152.

[0089] DSC method for melting point

[0090] According to ISO 11357-3, the melting point of samples weighing between 5 mg and 7 mg was measured under cooling and heating conditions in an inert N2 flow at a scan rate of 20°C / min. Indium was used for instrument calibration.

[0091] Melt flow rate: determined according to method ISO 1133 (230°C, 5 kg or 2.16 kg).

[0092] Inherent viscosity (IV)

[0093] The sample was dissolved in tetrahydronaphthalene at 135°C and then poured into a capillary viscometer. The viscometer tube (Ubbelohde type) was surrounded by a cylindrical glass jacket; this setup allows for temperature control using a circulating, constant-temperature liquid. The downward passage of the meniscus was timed by a photoelectric device.

[0094] The passage through the meniscus in front of the upper lamp starts a counter with a quartz crystal oscillator. When the lower lamp passes through, the meniscus stops the counter, and the outflow time is recorded: this is converted to an intrinsic viscosity value using Huggins' equation (Huggins, ML, *Journal of the American Chemical Society*, 1942, 64, 2716), provided that the flow time of the pure solvent is known under the same experimental conditions (same viscometer and same temperature). [η] is determined using a single polymer solution.

[0095] Ethylene content in copolymers

[0096] Acquired on a Bruker AV-600 spectrometer equipped with a cryoprobe. 13 The spectrometer was used for C NMR spectroscopy and operated at 160.91 MHz in Fourier transform mode at 120 °C.

[0097] The peak of Sββ carbon at 29.9 ppm (according to "Monomer Sequence Distribution in Ethylene-Propylene Rubber Measured by 13C NMR. 3. Use of Reaction Probability Mode"). 13 C10 NMR. 3. Use of Reaction Probability Mode (CJ Carman, R.A. Harrington, and C.E. Wilkes, *Macromolecules*, 1977, Vol. 10, p. 536) was used as an internal reference. The sample was dissolved at 120 °C in 1,1,2,2-tetrachloroethane-d2 at a concentration of 8 wt / v%. A 90° pulse was applied, with a 15-second delay between the pulse and the CPD to remove [reaction probability]. 1 H- 13 C-coupling was used to obtain each spectrum. 512 transients were stored in 32K data points using a spectral window of 9000Hz.

[0098] According to Kakugo ("Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titaniumtrichloride-diethylaluminum chloride", M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, *Macromolecules*, 1982, Vol. 15, p. 1150), the following equation was used to assign spectra, evaluate ternary distributions, and determine composition:

[0099] PPP = 100 Tββ / S PPE = 100 Tβδ / S EPE = 100 Tδδ / S

[0100] PEP = 100 Sββ / S PEE= 100 Sβδ / S EEE = 100 (0.25 Sγδ+0.5 Sδδ) / S

[0101] S = Tββ + Tβδ + Tδδ + Sββ + Sβδ + 0.25 Sγδ + 0.5 Sδδ

[0102] The molar percentage of ethylene content is evaluated using the following equation:

[0103] E% mol = 100 * [PEP+PEE+EEE]

[0104] The weight percentage of ethylene content is evaluated using the following equation:

[0105] 100 * E% mol * MWE

[0106] E% wt. = E% mol * MWE + P% mol * MWP

[0107] Where P% mol is the molar percentage of propylene content, and MWE and MWP are the molecular weights of ethylene and propylene, respectively.

[0108] Preparation of injection molded specimens: Obtain test specimens of 80 x 10 x 4 mm according to method ISO 1873-2:2007.

[0109] Flexural modulus: determined on injection molded test specimens according to method ISO 178:2019.

[0110] Tensile modulus: determined on an injection-molded test specimen according to method ISO 527-2.

[0111] Charpy impact test: Measured on injection-molded specimens according to ISO 179-1:2010.

[0112] Polydispersity index (PI): determined at 200°C using an RMS-800 parallel plate rheometer (sold by RHEOMETRICS, USA) operating at oscillation frequencies increasing from 0.1 radians / second to 100 radians / second. PI can be derived from the cross modulus using the following equation:

[0113] PI = 10⁵ / Gc

[0114] Where Gc is the cross modulus, which is defined as the value (in Pa) when G' = G”, where G' is the storage modulus and G” is the loss modulus.

[0115] Component A)

[0116] Preparation of solid catalyst components for component A)

[0117] 1000 mL of TiCl4 was introduced into a 2000 mL five-necked glass reactor equipped with a mechanical stirrer, jacket, and thermocouple, purged with nitrogen, and the reactor was cooled to -5 °C. While stirring, 60.0 g of microspheres MgCl2∙1.7C2H5OH (prepared according to the method described in Example 1 of EP728769) with an average particle size of 58 µm was added at -5 °C. The temperature was raised to 40 °C, and a certain amount of diethyl 2,3-diisopropylsuccinate was added to make the Mg / succinate molar ratio 13. The temperature was raised to 100 °C and maintained at this value for 60 minutes. After this, stirring was stopped for 15 minutes and the solid was allowed to settle. The liquid was siphoned off. After siphoning, fresh TiCl4 and a certain amount of 9,9-bis(methoxymethyl)fluorene were added to make the Mg / diether molar ratio 26. The temperature was then raised to 110 °C with stirring and maintained for 30 minutes. The reactor was then cooled to 75°C and stirring was stopped for 15 minutes. After precipitation and siphoning, fresh TiCl4 was added. The temperature was then raised to 90°C and the suspension was stirred for 15 minutes. The temperature was then lowered to 75°C and stirring was stopped for 15 minutes. After precipitation and siphoning, the solid was washed six times with anhydrous hexane (6 x 1000 ml) at 60°C and once with hexane at 25°C. The solid was dried in a rotary evaporator.

[0118] Preparation of catalyst system

[0119] Before introducing it into the polymerization reactor, the above solid catalyst components are contacted with triethylaluminum (TEAL) and dicyclopentyldimethoxysilane (DCPMS) at a temperature of 15°C.

[0120] Prepolymerization

[0121] The catalyst system was then prepolymerized at 20°C by suspending it in liquid propylene for 9 minutes before being introduced into the polymerization reactor.

[0122] The polymerization operation is carried out continuously in the polymerization equipment, as described in EP 1 012 195.

[0123] The catalyst was fed into a polymerization apparatus comprising two interconnected cylindrical reactors (a riser and a downcomer). Rapid fluidization conditions were established in the riser by recirculating gas from a gas-solid separator. Hydrogen was used as a molecular weight regulator. The polymerization conditions are reported in Table 1. Component A is the component A used in Example 1 of WO2016 / 050461.

[0124] Table 1

[0125]

[0126] C3 - =propylene

[0127] The properties of component A are reported in Table 2.

[0128] Table 2

[0129]

[0130] Component B)

[0131] Component B1) is a commercial heterogeneous polymer obtained by sequential gas-phase polymerization, which was used as component B in Example 1 of WO2016 / 050461.

[0132] Component B2) is a commercial heterogeneous polymer obtained through sequential gas-phase polymerization. The characteristics of the polymer marketed by LyondellBasell under the trade name X1956A are reported in Table 3.

[0133] Table 3

[0134]

[0135] * C2 = Ethylene-derived unit

[0136] Components A and B were blended in various percentages. The properties of the resulting blends are reported in Table 5 for comparison with those of Comparative Example 2.

[0137] Table 4

[0138]

[0139] *The remaining amount is component A. Comparative Example 3 is component A only.

[0140] As can be clearly seen from Table 4, the impact characteristics of blend 1 are higher than those of the control blend 2 and component A alone, while the flexural modulus and tensile modulus remain basically unchanged.

Claims

1. A polyolefin composition, said polyolefin composition comprising: A) 85% to 99.0% by weight of a propylene homopolymer, said propylene homopolymer having: (i) A polydispersity index ranging from 5 to 10; (ii) 4.0% by weight to 1.0% by weight of xylene solubles at 25°C, as determined by ISO 16 152; (iii) Melt flow rate (230°C / 5kg, ISO 1133), wherein the melt flow rate is in the range of 0.2 g / 10 min to 3.5 g / 10 min; B) A propylene-ethylene copolymer composition comprising 1.0% to 15.0% by weight, wherein the propylene-ethylene copolymer composition has the following characteristics: i) Fractions soluble in xylene at 25°C, ranging from 20% to 38% by weight as defined in ISO 16 152; ii) Melt flow rate (230°C / 0.16 kg, ISO 1133), wherein the melt flow rate ranges from 0.4 g / 10 min to 4.0 g / 10 min; iii) The intrinsic viscosity of the fraction soluble in xylene at 25°C, ranging from 5.7 dl / g to 9.2 dl / g, said intrinsic viscosity being measured in tetrahydronaphthalene at 135°C using the method reported in the specification; Component B of the propylene-ethylene copolymer composition comprises: b1) 27% to 40% by weight of propylene homopolymer, wherein the melt flow rate MFR1 (230°C / 2.16 kg, ISO 1133) of the propylene homopolymer ranges from 62.0 g / 10 min to 100.0 g / 10 min; b2) 27% to 40% by weight of propylene homopolymer, wherein the melt flow rate MFR2 (230°C / 2.16 kg, ISO 1133) of the propylene homopolymer is less than MFR1; b3) 20% to 46% by weight of a propylene-ethylene copolymer, wherein the ethylene-derived unit content of the propylene-ethylene copolymer ranges from 18.0% to 48.0% by weight. The melt flow rate (230°C / 5kg, ISO 1133) of the polyolefin composition ranges from 0.4 g / 10 min to 4.0 g / 10 min; the sum of A+B is 100% by weight and the sum of b1+b2+b3 is 100% by weight.

2. The polyolefin composition according to claim 1, wherein component A) ranges from 90% to 98.5% by weight, and component B) ranges from 1.5% to 10.0% by weight.

3. The polyolefin composition according to claim 1 or 2, wherein in component B), b1) ranges from 29% to 38% by weight; b2) ranges from 29% to 38% by weight; and component b3) ranges from 24% to 42% by weight.

4. The polyolefin composition according to any one of claims 1 to 4, wherein the melt flow rate of component B (230°C / 2.16 kg, ISO 1133) ranges from 0.6 g / 10 min to 3.0 g / 10 min.

5. The polyolefin composition according to any one of claims 1 to 5, wherein the intrinsic viscosity of the fraction that is soluble in xylene at 25°C, as measured in tetrahydronaphthalene, is in the range of 6.0 dl / g to 8.75 dl / g.

6. The polyolefin composition according to any one of claims 1 to 5, wherein the fraction in component B) that is soluble in xylene at 25°C ranges from 22.0% by weight to 36.0% by weight.

7. The polyolefin composition according to any one of claims 1 to 6, wherein the melt flow rate MFR1 (230°C / 2.16 kg, ISO 1133) of component b1) in component B) ranges from 72 g / 10 min to 87 g / 10 min.

8. The polyolefin composition according to any one of claims 1 to 7, wherein in component B), the melt flow rate MFR2 (230°C / 2.16 kg, ISO 1133) of component b2) is less than MFR1 - 40 g / 10 min.

9. The polyolefin composition according to any one of claims 1 to 8, wherein in component B), component b3) has an ethylene-derived unit content ranging from 22% to 44% by weight.

10. The polyolefin composition according to any one of claims 1 to 9, wherein the melt flow rate (230°C / 5 kg, ISO 1133) of the polyolefin composition is in the range of 0.7 g / 10 min to 3.2 g / 10 min.

11. The polyolefin composition according to any one of claims 1 to 10, wherein the soluble content in xylene in component A) at 25°C ranges from 3.0% by weight to 2.0% by weight.

12. The polyolefin composition according to any one of claims 1 to 11, wherein component A) ranges from 93% to 98% by weight, and component B) ranges from 2.0% to 7.0% by weight.

13. The polyolefin composition according to any one of claims 1 to 12, wherein component B) has a fraction ranging from 25.0% to 33.0% by weight of said fraction that is soluble in xylene at 25°C.

14. The polyolefin composition according to any one of claims 1 to 13, wherein component B) has the intrinsic viscosity of the fraction that is soluble in xylene at 25°C, measured in tetrahydronaphthalene, ranging from 6.2 dl / g to 8.2 dl / g.

15. A pipe comprising the polyolefin composition according to claims 1 to 14.

Citation Information

Patent Citations

  • Components and catalysts for the polymerization of olefins

    EP0045977A2

  • Process and apparatus for the gas-phase polymerisation

    EP1012195A1

  • Catalyst components and catalysts for the polymerization of alpha-olefins

    US4399054A

  • Components and catalysts for the polymerization of olefins

    US4472524A

  • Multilayer pipe

    WO1997033117A1